2021
DOI: 10.1093/mnras/stab1938
|View full text |Cite
|
Sign up to set email alerts
|

A systematic reclassification of Type IIn supernovae

Abstract: Type IIn supernovae (SNe IIn) are a relatively infrequently observed subclass of SNe whose photometric and spectroscopic properties are varied. A common thread among SNe IIn are the complex multiple-component hydrogen Balmer lines. Owing to the heterogeneity of SNe IIn, online databases contain some outdated, erroneous, or even contradictory classifications. SN IIn classification is further complicated by SN “impostors” and contamination from underlying H ii regions. We have compiled a catalogue of systematica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 128 publications
0
13
0
Order By: Relevance
“…The wind velocity, v w , for such SNe can typically vary between 30-600 kms −1 [63]. Their progenitors are not well known and have been found to be connected to LBV, Red Supergiant (RGB) and Yellow Hypergiant (YHG) stars (see e.g., [116][117][118][119] and references therein). These stars have large mass loss rates ( ṀW ∼ 10 −3 -10 1 M yr −1 ) and moderate wind velocity (v w ∼ 100 kms −1 ) [63,120].…”
Section: Young Supernova Typesmentioning
confidence: 99%
“…The wind velocity, v w , for such SNe can typically vary between 30-600 kms −1 [63]. Their progenitors are not well known and have been found to be connected to LBV, Red Supergiant (RGB) and Yellow Hypergiant (YHG) stars (see e.g., [116][117][118][119] and references therein). These stars have large mass loss rates ( ṀW ∼ 10 −3 -10 1 M yr −1 ) and moderate wind velocity (v w ∼ 100 kms −1 ) [63,120].…”
Section: Young Supernova Typesmentioning
confidence: 99%
“…As shown in the model suite of Dessart et al (2010), more massive (M 25 M ) stars tend to be more compact and the binding energy of the hydrogen envelope can be orders of magnitude higher. Observationally, the diverse photometric and spectroscopic features observed among Type IIn SNe also point to a wide range of progenitor and environment properties (Miller et al 2010;Kiewe et al 2012;Gangopadhyay et al 2020;Nyholm et al 2020;Ransome et al 2021). It will be informative to explore how mass loss and ejecta properties depend on the stellar models.…”
Section: Caveats and Future Directionsmentioning
confidence: 99%
“…While most theoretical studies modeled energy deposition and mass-erupting outbursts in 1D, polarimetry observations have shown that interacting SNe can be considerably asymmetric (Patat et al 2011;Levesque et al 2014;Mauerhan et al 2014;Reilly et al 2017). Their diverse light curve and spectral features also point to intrinsically complex CSM geometries (Kiewe et al 2012;Soumagnac et al 2019;Nyholm et al 2020;Ransome et al 2021). In fact, 3D radiation hydrodynamical simulations of RSG envelopes have shown that convection can produce shocks and inhomogeneous large eddies near the surface (Chiavassa et al 2009(Chiavassa et al , 2011, and that above a certain critical radius radiative loss in the convective layer can render the usual mixing length theory (MLT) description inaccurate (Goldberg et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Often, non-terminal events such as luminous red novae (LRNe) or LBV outbursts are classified as Type IIn events due to the narrow Hα component (Ransome et al 2021). Referred to as "SN imposters" (Van Dyk et al 2000;Smith et al 2011;Kochanek et al 2012;Van Dyk & Matheson 2012;Pastorello et al 2019), their fainter absolute magnitudes at maximum light, −10 < M V < −15 mag, generally differentiate them from terminal IIn events.…”
Section: Introductionmentioning
confidence: 99%